(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
One of the most important actual problems of Serviceology is the definition of essence human needs, their classification and the creation of their satisfaction system. To solve these problems it is suggested to use systematic approach which will give the opportunity to create sustainable system of human needs satisfaction.